G=
[tex](x + 3)(x + 4) \\ = x {}^{2} + 4x + 3x + 12 \\ = x {}^{2} + 7x + 12[/tex]
H=
[tex](x - 3)(x + 6) \\ = x {}^{2} + 6x - 3x - 18 \\ = x { }^{2} + 3x - 18[/tex]
I=
[tex](x - 1)(x - 5) \\ = x {}^{2} - 5x - x + 5 \\ = x {}^{2} - 6x + 5[/tex]
J=
[tex](x + \frac{1}{3} )(x - \frac{7}{11}) \\ = x {}^{2} - \frac{7}{11}x + \frac{1}{3} x - \frac{7}{33} \\ = x {}^{2} - \frac{21}{33} x + \frac{11}{33} x - \frac{7}{33} \\ = x {}^{2} - \frac{10}{33} x - \frac{7}{33} [/tex]
K=
[tex](x + 2)(x + 4) + 5x {}^{2} - 3x - 6 \\ = {x}^{2} + 4x + 2x + 8 + 5 {x}^{2} - 3x - 6 \\ = 6 {x}^{2} + 3x + 2[/tex]
L=
[tex](x - 3)(2x + 6) - 4(x - 2) \\ = 2x ^{2} + 6x - 6x - 18 - 4x + 8 \\ = 2x ^{2} - 4x - 10[/tex]
M=x^3+2x^2-4x-x^2-2x+4
=x^3+x^2-6x+4